2018
DOI: 10.1093/cid/ciy244
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Safety and Immunogenicity of Tetanus, Diphtheria, and Acellular Pertussis Vaccine Immunization During Pregnancy and Subsequent Infant Immune Response

Abstract: NCT00553228.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 30 publications
6
113
0
6
Order By: Relevance
“…No significant increase in any of these outcomes were identified among infants of Tdap-vaccinated compared to non-vaccinated pregnant women, or from expected norms, regardless of design (database analysis vs. clinical trial), population, or setting [13,41,43,50,[52][53][54][55][56]58]. In addition, no differences in the rates of serious adverse outcomes were observed in infants of Tdap-and Td-vaccinated pregnant women, and none of the serious adverse outcomes reported were considered related to vaccination [35]. Hoang et al [36] reported that infants of Tdapvaccinated women presented common symptoms of respiratory and gastrointestinal diseases, although no events were serious or considered related to vaccination.…”
Section: Adverse Birth and Neonatal Outcomes/ Complicationsmentioning
confidence: 86%
See 3 more Smart Citations
“…No significant increase in any of these outcomes were identified among infants of Tdap-vaccinated compared to non-vaccinated pregnant women, or from expected norms, regardless of design (database analysis vs. clinical trial), population, or setting [13,41,43,50,[52][53][54][55][56]58]. In addition, no differences in the rates of serious adverse outcomes were observed in infants of Tdap-and Td-vaccinated pregnant women, and none of the serious adverse outcomes reported were considered related to vaccination [35]. Hoang et al [36] reported that infants of Tdapvaccinated women presented common symptoms of respiratory and gastrointestinal diseases, although no events were serious or considered related to vaccination.…”
Section: Adverse Birth and Neonatal Outcomes/ Complicationsmentioning
confidence: 86%
“…Injection site reactions assessed over 7 days were more common after Tdap than placebo in one small clinical study [13] but occurred at similar rates over 48 h in another slightly larger study [40]. Systemic and local reactions occurred at similar frequencies in pregnant women receiving Tdap and those receiving tetanus vaccines in two clinical studies [35,36]. For infants admitted to NICU, number of days in the unit (p = 0.001) and frequency of admission for preterm birth (p = 0.03) or anemia (p = 0.03) lower for Tdap vs.…”
Section: Vaccine Reactogenicity In Pregnant Womenmentioning
confidence: 93%
See 2 more Smart Citations
“…We defined blunting as reported statistically significant lower GMC levels (based on non-overlapping 95% confidence intervals (CI) or p-values) against antigens included in DTaPcontaining vaccines when comparing immunogenicity in infants born to mothers who were vaccinated with Tdap-containing vaccines during pregnancy to a control group (infants born to mothers not exposed to Tdap during pregnancy) after primary immunization and/or booster dose. Of note, several papers reported significant p-values (p < 0.05) with overlapping 95% CI [19][20][21][22][23][24][25]. We adopted the approach to consider these papers as reporting statistically significant lower GMC levels between the two groups and provided point estimates and 95% CI (Table 2) for readers to make their own assessment whether the reported statistical significance refers to a real difference in GMC levels or haphazard reporting.…”
Section: Methodsmentioning
confidence: 99%